The SAGES Manual of Hernia Repair - Jacob, Brian P.; Ramshaw, Bruce (Springer New York : Imprint: Springer, 2013)
The SAGES Manual of Hernia Repair will serve as a state-of-the-art resource for hernia surgeons and residents alike who are interested in the rapidly evolving area of abdominal wall hernia repair. This manual captures and summarizes the current trends in the field, as well as describing the new ideas, programs, and strategies regarding hernia repair. Through a unique section called Current Debates in Inguinal Hernia Repair, this volume also provides readers an overview of the current opinions on many of the ongoing debates of this time period. Furthermore, the manual is lavishly illustrated, containing an array of instructional charts and photographs, and is authored by a panel of experts in hernia repair. Comprehensive and easily accessible, The SAGES Manual of Hernia Repair is a portable reference that will be of great value to all practicing surgeons and residents working in the field of abdominal wall hernia repair.